Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Insights Into the Experiences of People Living With Chronic Kidney Disease and Obesity Participating in a Randomized Controlled Weight Loss Trial: A Qualitative Study - Marguerite Conley; Nicole Scholes-Robertson; Soraya Cunningham; Hannah L. Mayr; Kirsten Hepburn; David W. Mudge; Justin Holland; Tammy Tonges; David W. Johnson; Andrea K. Viecelli; Helen L. MacLaughlin (Journal of the Academy of Nutrition and Dietetics, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Modulation of the nociceptive withdrawal reflex in walking is not changed by the presence of tonic pain - Joanna Reeves; Connor Thacker; Geoffrey Cunningham; Sam Hughes; Jennifer L. Davies (Experimental Brain Research, 2026)
Tonic pain inhibits the nociceptive withdrawal reflex (NWR). NWR magnitude varies across the gait cycle, but it is unknown whether tonic pain affects this phase-dependent modulation of the NWR during walking. Sixteen healthy participants (mean ± SD age: 29 ± 9 years, 3 males) walked on a treadmill with and without tonic pain applied to the left arm. Lower-limb kinematics and electromyography (EMG) from bilateral biceps femoris, vastus lateralis, soleus and tibialis anterior were recorded. At predefined points in the gait cycle, a brief electrical stimulus was applied to the arch of the right foot to elicit an NWR. Reflex responses were calculated from the EMG as a percentage difference to the EMG present without any stimulation. There was a significant effect of gait phase on reflex response in all muscles except ipsilateral biceps femoris. When accounting for the intensity of tonic pain, there was a 0.64 decrease in normalised reflex response in the contralateral tibialis anterior with tonic pain versus control ( p = 0.009). There were no other effects of tonic pain on reflex response ( p > 0.05). There was an increase in knee flexion on the stimulated leg when it was unloading, however there was large variability in the kinematics. Stimulation during loading response saw around a 3° increase ( p = 0.007) in dorsiflexion in the contralateral leg. Our findings suggest that tonic pain does not influence the modulation of the NWR during walking. We propose that the need to maintain balance overrides any effects of endogenous pain modulation.

Chemogenetic inhibition of the anterior cingulate cortex increases safe decision-making in aged mice performing the Iowa Gambling Task - Benjamin Z. Roberts; M. Melissa Flesher; Landon F. Cunningham; Adam L. Halberstadt; Jared W. Young (Psychopharmacology, 2026)

Revisiting evolutionary rescue in the wild - Laurinne J. Balstad; Marissa L. Baskett; Stephanie M. Carlson; Curry J. Cunningham; Peter A.H. Westley (Trends in Ecology & Evolution, 2026)

Evaluation of anti-desmoglein-2 antibodies and cardiac biomarkers in Boxer dogs with arrhythmogenic right ventricular cardiomyopathy - L. Dos Santos; S. Cunningham; M. Mantovani (Journal of Veterinary Cardiology, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

Food variety affects food selection and variety-seeking behaviors in an immersive virtual reality food buffet - John W. Long; Paige M. Cunningham; Kathleen L. Keller; Barbara J. Rolls; Travis D. Masterson (Appetite, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Sensory-specific satiety and the influence of variety on snack intake in school-aged children - Paige M. Cunningham; Cara T. Meehan; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2026)

The SPoRC Stock Assessment Package: A Generalized Next‐Generation Platform to Assess Spatial, Age and Sex‐Structured Populations - Matthew LH. Cheng; Daniel R. Goethel; Curry J. Cunningham; Peter‐John F. Hulson; James N. Ianelli; Kristen L. Omori (Fish and Fisheries, 2026)
Fisheries managers increasingly rely on stock assessment models to provide sustainable management advice, which must balance complex and competing objectives. Although assessment models necessitate simplifying assumptions, there is increasing recognition to improve the integration of realistic biological and fishery dynamics. While ongoing and future development of increasingly complex stock assessments requires increased capacity (i.e., time, training, and personnel), there are concerns that the growing demand for assessment advice cannot be adequately fulfilled under current resources. To address these needs, we present the Stochastic Population over Regional Components (SPoRC) model, a modern integrated analysis platform that is generalized, modular and developed in a user‐friendly programming language (R with Template Model Builder, RTMB). Development of SPoRC emphasized consideration of age, sex, and spatial dynamics at the outset, while ensuring the ability to integrate diverse data sources (e.g., catch, abundance indices, age/length compositions and tagging). Moreover, state‐space specification of time‐varying processes through random effects and robust simulation capabilities were primary design features. Here, we highlight SPoRC's utility in cohesively implementing single‐and multi‐region applications, its ability to estimate time‐varying processes as random effects, and the potential to conduct closed‐loop simulations for evaluating the robustness of management procedures. By developing a generalized assessment platform in a user‐friendly R package, we suggest that SPoRC reduces barriers to implementation of next‐generation stock assessment models and facilitates team‐based model development, which will ultimately help improve the capacity to implement stock assessments globally.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Blood–Brain Barrier Permeability in Cases of Post-operative Delirium Is Associated with Central Nervous System Phosphatidylcholine Imbalances - Mijin Jung; Xiaobei Pan; Aoife Sweeney; Anthony P. Passmore; Bernadette McGuinness; Daniel F. McAuley; David Beverland; Amanda J. Heslegrave; Jonathan Schott; Henrik Zetterberg; Emma L. Cunningham; Brian D. Green (Molecular Neurobiology, 2026)
Blood-brain barrier (BBB) permeability is reportedly increased in patients exhibiting postoperative delirium. Changes in either cerebrospinal fluid (CSF) or blood metabolites have also been reported in cases of delirium. This investigation examined whether BBB permeability influences metabolite concentrations on either side of the barrier, and whether this changes in cases of delirium. This study is a nested case-control cohort ( n = 54) drawn from the entire cohort of n = 315 participants. Preoperative CSF and plasma from postoperative delirium and control participants matched for age and gender underwent metabolomic profiling. Concentrations of metabolites in plasma and in CSF were obtained, and where measurable, a CSF/plasma metabolite ratio (Qmetab) was calculated. CSF/plasma albumin ratio (Qalb), a recognized indicator of BBB permeability, was also calculated. The above parameters were compared between delirium and control groups. Finally, each Qmetab was correlated against Qalb for control or delirium cases. In cases where delirium would later occur there were significant elevations in the Qmetabs of amino acids (Gln, His, Met, Phe, Tyr and Val), and one phosphatidylcholine (PC). Many other PC Qmetabs significantly correlated with Qalb and this mainly occurred in individuals subsequently experiencing delirium. In persons prone to postoperative delirium, the equilibrium of certain species of PC across the BBB correlates with BBB permeability. It is unclear whether this occurs because of changes in PC metabolism or transit, but understanding this could improve our understanding of the mechanisms underlying delirium.

Forward osmosis followed by reverse osmosis for the removal of contaminants of emerging concern using a CO2-responsive draw agent - Rachel S. Korchinsky; José Giovanni L. Brito; Louis Fieldhouse; Pascale Champagne; Michael F. Cunningham; Philip G. Jessop (Journal of Hazardous Materials, 2025)

Carbon dioxide removal during dissolution of granular basalt: A mass balance test of enhanced rock weathering at the hillslope scale - Charles J. Cunningham; Andrew Guertin; Marine Gelin; Louis A. Derry; Hannes H. Bauser; Minseok Kim; Jennifer L. Druhan; Scott Saleska; Peter A. Troch; Jon Chorover (Earth and Planetary Science Letters, 2025)

Drivers and Dynamics of Salmon Bycatch in the Eastern Bering Sea Pollock Fishery - Lukas B. DeFilippo; Wesley A. Larson; Patrick D. Barry; Curry J. Cunningham; Joseph A. Langan; Sabrina Garcia; Kathrine G. Howard; James N. Ianelli; Diana L. Stram (Fish and Fisheries, 2025)
Minimising bycatch is a pervasive challenge for sustainable fisheries management, the importance of which is amplified for non‐target species or populations that are in decline. In the eastern Bering Sea (EBS) walleye pollock ( Gadus chalcogrammus ) fishery, salmon—most notably Chinook ( Oncorhynchus tshawytscha ) and chum ( O. keta )—are encountered as bycatch. Salmon bycatch in the EBS pollock fishery has become an issue of growing concern, largely due to declines in Western Alaska Chinook and chum salmon, which support directed fisheries vital to the wellbeing of regional communities. Consequently, minimising salmon bycatch is a management priority and requires information on the underlying processes driving encounters between salmon and pollock vessels. In this study, we present a broad synthesis of Chinook and chum salmon bycatch dynamics in the EBS pollock fishery. Applying a hierarchical modelling framework to nearly 120,000 catch records collected over 13 years (2011–2023), we quantify patterns of variation in salmon bycatch over space and time, and environmental drivers thereof. Our results reveal spatially structured, interannual variation in chum and Chinook salmon bycatch associated with oceanographic conditions. We also demonstrate the importance of interactions between bottom depth and local sea surface temperature anomalies in shaping bycatch rates, which vary across fishing seasons and salmon species. By advancing our understanding of the factors that contribute to encounters between pollock vessels and salmon, this study can inform ongoing management efforts aimed at minimising multispecies salmon bycatch in a changing marine ecosystem.

The Evaluation of Macronutrient Composition of Maternal Breast Milk and Pasteurized Donor Breast Milk to Optimize Nutrition and Growth for the NICU Infant - S. Dave; L. Cunningham (Journal of the Academy of Nutrition and Dietetics, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

High satiety: Evaluating determinants of energy compensation and intake in multiple preloading studies - Barbara J. Rolls; Liane S. Roe; Paige M. Cunningham; Kathleen L. Keller; Faris M. Zuraikat (Appetite, 2025)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Spatiotemporal drivers of rodenticide exposure in a mammalian forest carnivore - Stephanie A. Cunningham; Jacqueline L. Frair; Paul G. Jensen; Krysten L. Schuler (Science of The Total Environment, 2025)

Accumulation of benzotriazole UV-stabilizers in relation to ingested plastics and associated health metrics in Larus gulls feeding at a landfill in Atlantic Canada - Kerry Schutten; André Morrill; Zhe Lu; Akshaya Chandrashekar; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire M. Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Misspecifying Sex‐Structured Dynamics in Stock Assessment Models - Matthew L. H. Cheng; Daniel R. Goethel; Peter‐John F. Hulson; Michael J. Wilberg; Craig Marsh; Curry J. Cunningham (Fish and Fisheries, 2025)
Sex‐specific variation in population demography and life‐history traits (e.g., growth, natural mortality) is common in many fish populations. Differences in these processes by sex can dictate population dynamics and influence how harvesters interact with the resource. Across various fisheries management systems, stock assessment models (SAMs), which mathematically represent population age and/or size structure, are widely utilised to estimate fish population status and provide sustainable harvest recommendations. However, few studies have examined the implications of alternative modelling assumptions when incorporating sex‐specific dynamics in SAMs. For instance, the impacts of simultaneously ignoring sex‐specific variations in growth, selectivity, and natural mortality on SAM performance have not been explored. In this study, a simulation‐estimation framework was developed for a sexually dimorphic fish population to: (1) assess the consequences of ignoring sexual dimorphism (i.e., growth, natural mortality, and selectivity) and the benefits of using sex‐specific catch data to inform the estimation of these processes, (2) evaluate the implications of incorrect modelling assumptions regarding sex ratio at birth, and (3) develop advice for parameterising observation likelihoods to describe sex‐specific composition data. Correctly parameterising sex‐specific variation in life‐history traits led to more robust population estimates and catch advice. Conversely, SAMs ignoring these variations yielded biased estimates of biomass and harvest recommendations. Collectively, our results underscore that oversimplified assumptions about sex‐specific variations in SAMs can lead to poor management advice. Moreover, results emphasise the need for routine collection of sex‐specific data to support the development of biologically realistic models.

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Food switching at a meal is positively associated with change in adiposity among children at high-familial risk for obesity - Nicholas V. Neuwald; Alaina L. Pearce; Paige M. Cunningham; Marissa N. Setzenfand; Lauren Koczwara; Barbara J. Rolls; Kathleen L. Keller (Appetite, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Formation of vertical columnar seismic structures and seafloor depressions by groundwater discharge in the drowned Miami Terrace platform and overlying deep-water carbonates, southeastern Florida - Kevin J. Cunningham; Richard L. Westcott; Sean Norgard; Edward Robinson; Harry J. Dowsett; Marci M. Robinson (Marine Geology, 2024)

Advancing investigations into the effects of sweet and bitter tastes on agreeableness and hostility - Rachel S. Herz; Caitlin M. Cunningham; Theresa L. White (Food Quality and Preference, 2024)

Stable silicon isotope fractionation reflects the routing of water through a mesoscale hillslope - Andrew Guertin; Charlie Cunningham; Julien Bouchez; Marine Gelin; Jon Chorover; Hannes Bauser; Minseok Kim; Peter Troch; Louis A. Derry; Jennifer L. Druhan (Earth and Planetary Science Letters, 2024)

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Body size and early marine conditions drive changes in Chinook salmon productivity across northern latitude ecosystems - Megan L. Feddern; Rebecca Shaftel; Erik R. Schoen; Curry J. Cunningham; Brendan M. Connors; Benjamin A. Staton; Al von Finster; Zachary Liller; Vanessa R. von Biela; Katherine G. Howard (Global Change Biology, 2024)
Disentangling the influences of climate change from other stressors affecting the population dynamics of aquatic species is particularly pressing for northern latitude ecosystems, where climate‐driven warming is occurring faster than the global average. Chinook salmon ( Oncorhynchus tshawytscha ) in the Yukon‐Kuskokwim (YK) region occupy the northern extent of their species' range and are experiencing prolonged declines in abundance resulting in fisheries closures and impacts to the well‐being of Indigenous people and local communities. These declines have been associated with physical (e.g., temperature, streamflow) and biological (e.g., body size, competition) conditions, but uncertainty remains about the relative influence of these drivers on productivity across populations and how salmon–environment relationships vary across watersheds. To fill these knowledge gaps, we estimated the effects of marine and freshwater environmental indicators, body size, and indices of competition, on the productivity (adult returns‐per‐spawner) of 26 Chinook salmon populations in the YK region using a Bayesian hierarchical stock‐recruitment model. Across most populations, productivity declined with smaller spawner body size and sea surface temperatures that were colder in the winter and warmer in the summer during the first year at sea. Decreased productivity was also associated with above average fall maximum daily streamflow, increased sea ice cover prior to juvenile outmigration, and abundance of marine competitors, but the strength of these effects varied among populations. Maximum daily stream temperature during spawning migration had a nonlinear relationship with productivity, with reduced productivity in years when temperatures exceeded thresholds in main stem rivers. These results demonstrate for the first time that well‐documented declines in body size of YK Chinook salmon were associated with declining population productivity, while taking climate into account.

Plastic ingestion, accumulated heavy metals, and health metrics of four Larus gull species feeding at a coastal landfill in eastern Canada - Kerry Schutten; André Morrill; Akshaya Chandrashekar; Brian Stevens; E. Jane Parmley; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2024)

Changing disturbance regimes, material legacies, and stabilizing feedbacks: Dead coral skeletons impair key recovery processes following coral bleaching - Kai L. Kopecky; Sally J. Holbrook; Emalia Partlow; Madeline Cunningham; Russell J. Schmitt (Global Change Biology, 2024)
Ecosystem responses to disturbance depend on the nature of the perturbation and the ecological legacies left behind, making it critical to understand how climate‐driven changes in disturbance regimes modify resilience properties of ecosystems. For coral reefs, recent increases in severe marine heat waves now co‐occur with powerful storms, the historic agent of disturbance. While storms kill coral and remove their skeletons, heat waves bleach and kill corals but leave their skeletons intact. Here, we explored how the material legacy of dead coral skeletons modifies two key ecological processes that underpin coral reef resilience: the ability of herbivores to control macroalgae (spatial competitors of corals), and the replenishment of new coral colonies. Our findings, grounded by a major bleaching event at our long‐term study locale, revealed that the presence of structurally complex dead skeletons reduced grazing on turf algae by ~80%. For macroalgae, browsing was reduced by >40% on less preferred (unpalatable) taxa, but only by ~10% on more preferred taxa. This enabled unpalatable macroalgae to reach ~45% cover in 2 years. By contrast, herbivores prevented macroalgae from becoming established on adjacent reefs that lacked skeletons. Manipulation of unpalatable macroalgae revealed that the cover reached after 1 year (~20%) reduced recruitment of corals by 50%. The effect of skeletons on juvenile coral growth was contingent on the timing of settlement relative to the disturbance. If corals settled directly after bleaching (before macroalgae colonized), dead skeletons enhanced colony growth by 34%, but this benefit was lost if corals colonized dead skeletons a year after the disturbance once macroalgae had proliferated. These findings underscore how a material legacy from a changing disturbance regime can alter ecosystem resilience properties by disrupting key trophic and competitive interactions that shape post‐disturbance community dynamics.

Switching between foods is reliably associated with intake across eating events in children - N.V. Neuwald; A.L. Pearce; P.M. Cunningham; L. Koczwara; M.N. Setzenfand; B.J. Rolls; K.L. Keller (Appetite, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Economic impacts of marine debris encounters on commercial shrimping - Benedict C. Posadas; Eric L. Sparks; Sarah R. Cunningham; Alyssa E. Rodolfich; Caitlin Wessel; Ryan Bradley (Marine Pollution Bulletin, 2024)

Poorer inhibitory control was related to greater food intake across meals varying in portion size: A randomized crossover trial - Paige M. Cunningham; Liane S. Roe; Alaina L. Pearce; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2024)

Chemical cues of conspecific predation elicit distinct behavioural responses in cannibalistic poison frog tadpoles - Lisa L. Surber-Cunningham; Samta S. Oza; Eva K. Fischer (Animal Behaviour, 2024)

Variety and portion size combine to increase food intake at single-course and multi-course meals - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

A co-design method for including stakeholder perspectives in nature-based flood risk management - Jill H. Slinger; Scott C. Cunningham; Baukje L. M. Kothuis (Natural Hazards, 2023)
Intervention methods to establish commitment to (collaborative) action are of potential interest to researchers and policymakers intent upon including stakeholder perspectives in natural risk governance (Scolobig, Nat Hazards 81:27–43, 2016). In this paper, a 6-step co-design method for engaging with local people in collaboratively envisioning nature-based solutions for flood defence is described. The problem structuring base of the participatory method is extended to accommodate the multi-actor situation and the local context of flood risk management. The intervention method is applied in a workshop in the Houston–Galveston Bay area in October 2014. At that time there was strong contestation surrounding the proposed Ike Dike with alternative combinations of nature-based and smaller conventional engineering solutions being proposed. The results indicate that the local participants were able to envision a wide range of future outcomes for the bay and were able to use the insights on nature-based solutions and the social contacts that they acquired at the transdisciplinary workshop to mobilize commitment to joint action. This action focused on collaboration rather than specifying ecological or technical infrastructural requirements and was instrumental in initiating more open discourse on flood defence options for the Houston–Galveston Bay area. The paper concludes that the generic applicability of the co-design method is limited by the requirement to understand and accommodate local circumstances and participants’ insights within the workshop.

A trait-based assessment of southern African arid-zone birds' vulnerability to climate change - Stephanie L. Payne; Susan J. Cunningham; Caroline G. Howes; Andrew E. McKechnie (Biological Conservation, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

A novel climate and health decision support platform: Approach, outputs, and policy considerations - Jeremy J. Hess; Timothy J. Sheehan; Alyssa Miller; Rad Cunningham; Nicole A. Errett; Tania Busch Isaksen; Jason Vogel; Kristie L. Ebi (Environmental Research, 2023)

Switching between bites of food and sips of water is related to food intake across meals varying in portion size - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Anouk E.M. Hendriks-Hartensveld; Barbara J. Rolls (Appetite, 2023)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Pulses of anthropogenic food availability appear to benefit parents, but compromise nestling growth in urban red-winged starlings - Sarah Catto; Petra Sumasgutner; Arjun Amar; Robert L. Thomson; Susan J. Cunningham (Oecologia, 2021)
The provision of anthropogenic food undoubtedly influences urban bird fitness. However, the nature of the impact is unclear, with both benefits and costs of urban diets documented. Moreover, the influence of short-term fluctuations in food availability, linked to urban weekday/weekend cycles of human presence, is largely unknown. We explored whether breeding red-winged starlings Onychognathus morio in Cape Town, South Africa, altered foraging and provisioning behaviour between days with high human presence (HHP) and days with low human presence (LHP)—i.e. weekdays versus weekends and vacation days. We investigated the relationship between starling diet, adult body mass and nestling development. Breeding adults consumed and provisioned the same quantity of food, but a significantly greater proportion of anthropogenic food on HHP compared to LHP days. Adults apparently benefited from the anthropogenic diet, experiencing significantly greater mass gain on HHP days. However, nestlings experienced a cost, with the number of HHP days during the nestling period associated negatively with nestling size. Adults may, therefore, benefit from the high calorie content of anthropogenic food, while nestlings may be negatively affected by nutrient limitation. The quantity of food available in urban environments may, therefore, benefit adult survival, while its quality imposes a cost to nestling growth.

A pilot study of a culturally-appropriate, educational intervention to increase participation in cancer clinical trials among African Americans and Latinos - Jennifer Cunningham-Erves; Tilicia L. Mayo-Gamble; Pamela C. Hull; Tao Lu; Claudia Barajas; Caree R. McAfee; Maureen Sanderson; Juan R. Canedo; Katina Beard; Consuelo H. Wilkins (Cancer Causes & Control, 2021)

Ordovician volcanic rocks record rifting, Variscan metamorphism and gold mineralization processes (Truchas Syncline, NW Iberia, Spain) - L. González-Menéndez; F. Gómez-Fernández; J. K. Cunningham; S. Menéndez; P. Caldevilla; G. Gallastegui; A. Cuesta (Journal of Iberian Geology, 2021)

Morphine and ethanol pretreatment effects on expression and extinction of ethanol-induced conditioned place preference and aversion in mice - Christopher L. Cunningham; Lee Bakner; Lindsey M. Schuette; Emily A. Young (Psychopharmacology, 2021)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Inferring seasonal infection risk at population and regional scales from serology samples - Mark Q. Wilber; Colleen T. Webb; Fred L. Cunningham; Kerri Pedersen; Xiu‐Feng Wan; Kim M. Pepin (Ecology, 2020)
Accurate estimates of seasonal infection risk can be used by animal health officials to predict future disease risk and improve understanding of the mechanisms driving disease dynamics. It can be difficult to estimate seasonal infection risk in wildlife disease systems because surveillance assays typically target antibodies (serosurveillance), which are not necessarily indicative of current infection, and serosurveillance sampling is often opportunistic. Recently developed methods estimate past time of infection from serosurveillance data using quantitative serological assays that indicate the amount of antibodies in a serology sample. However, current methods do not account for common opportunistic and uneven sampling associated with serosurveillance data. We extended the framework of survival analysis to improve estimates of seasonal infection risk from serosurveillance data across population and regional scales. We found that accounting for the right‐censored nature of quantitative serology samples greatly improved estimates of seasonal infection risk, even when sampling was uneven in time. Survival analysis can also be used to account for common challenges when estimating infection risk from serology data, such as biases induced by host demography and continually elevated antibodies following infection. The framework developed herein is widely applicable for estimating seasonal infection risk from serosurveillance data in humans, wildlife, and livestock.

Demodicosis in a captive African straw-coloured fruit bat (Eidolon helvum) - Carlo Bianco; Kate S. Baker; Luca Pazzini; Alessandra Cafiso; Richard D. Suu-Ire; Andrew A. Cunningham; James L. N. Wood; Alejandro Nuñez (Experimental and Applied Acarology, 2019)

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles - Brittany N. J. Davis; Jeffrey W. Santoso; Michaela J. Walker; Catherine E. Oliver; Michael M. Cunningham; Christian A. Boehm; Danielle Dawes; Samantha L. Lasater; Kim Huffman; William E. Kraus; George A. Truskey (Annals of Biomedical Engineering, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Effects of multi-modal cues on conditioned place preference in C57BL/6J and DBA/2J mice - Christopher L. Cunningham; Chloe N. Shields (Psychopharmacology, 2018)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

Naloxone effects on extinction of ethanol- and cocaine-induced conditioned place preference in mice - Laura Font; Christa A. Houck; Christopher L. Cunningham (Psychopharmacology, 2017)

Interaction rewiring and the rapid turnover of plant–pollinator networks - Paul J. CaraDonna; William K. Petry; Ross M. Brennan; James L. Cunningham; Judith L. Bronstein; Nickolas M. Waser; Nathan J. Sanders (Ecology Letters, 2017)
Whether species interactions are static or change over time has wide‐reaching ecological and evolutionary consequences. However, species interaction networks are typically constructed from temporally aggregated interaction data, thereby implicitly assuming that interactions are fixed. This approach has advanced our understanding of communities, but it obscures the timescale at which interactions form (or dissolve) and the drivers and consequences of such dynamics. We address this knowledge gap by quantifying the within‐season turnover of plant–pollinator interactions from weekly censuses across 3 years in a subalpine ecosystem. Week‐to‐week turnover of interactions (1) was high, (2) followed a consistent seasonal progression in all years of study and (3) was dominated by interaction rewiring (the reassembly of interactions among species). Simulation models revealed that species’ phenologies and relative abundances constrained both total interaction turnover and rewiring. Our findings reveal the diversity of species interactions that may be missed when the temporal dynamics of networks are ignored.

Clinostomum album n. sp. and Clinostomum marginatum (Rudolphi, 1819), parasites of the great egret Ardea alba L. from Mississippi, USA - Thomas G. Rosser; Neely R. Alberson; Ethan T. Woodyard; Fred L. Cunningham; Linda M. Pote; Matt J. Griffin (Systematic Parasitology, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Development of a Theory-based, Sociocultural Instrument to Assess Black Maternal Intentions to Vaccinate Their Daughters Aged 9 to 12 Against HPV - Jennifer Cunningham-Erves; Laura L. Talbott; Marcia R. O’Neal; Nataliya V. Ivankova; Kenneth A. Wallston (Journal of Cancer Education, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Warfare in stingless bees - C. Grüter; L. G. von Zuben; F. H. I. D. Segers; J. P. Cunningham (Insectes Sociaux, 2016)

Groundwater availability in the United States: the value of quantitative regional assessments - Kevin F. Dennehy; Thomas E. Reilly; William L. Cunningham (Hydrogeology Journal, 2015)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Cell adhesion properties of neural stem cells in the chick embryo - David R. Canning; Rebecca L. Cunningham (In Vitro Cellular & Developmental Biology - Animal, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Psittacine beak and feather disease in a free-living ring-necked parakeet (Psittacula krameri) in Great Britain - Ricardo C. C. Sa; Andrew A. Cunningham; Mark P. Dagleish; Nick Wheelhouse; Ann Pocknell; Nicole Borel; Hannah L. Peck; Becki Lawson (European Journal of Wildlife Research, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Effects of acute withdrawal on ethanol-induced conditioned place preference in DBA/2J mice - Sarah E. Dreumont; Christopher L. Cunningham (Psychopharmacology, 2014)

Effects of dopamine receptor antagonists on the acquisition of ethanol-induced conditioned place preference in mice - Melanie M. Pina; Christopher L. Cunningham (Psychopharmacology, 2014)

3rd Annual Conference of the Leverhulme Centre for Integrative Research on Agriculture and Health (LCIRAH), Developing methods in agriculture and health research, London, 13–14 June 2013 - Jody Harris; Mieghan Bruce; Elisa Cavatorta; Laura Cornelsen; Barbara Häsler; Rosie Green; Emily H. Morgan; Sara Stevano; Helen L. Walls; Kenda Cunningham (Food Security, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

The costs of keeping cool in a warming world: implications of high temperatures for foraging, thermoregulation and body condition of an arid‐zone bird - Katherine L. du Plessis; Rowan O. Martin; Philip A. R. Hockey; Susan J. Cunningham; Amanda R. Ridley (Global Change Biology, 2012)
Recent mass mortalities of bats, birds and even humans highlight the substantial threats that rising global temperatures pose for endotherms. Although less dramatic, sublethal fitness costs of high temperatures may be considerable and result in changing population demographics. Endothermic animals exposed to high environmental temperatures can adjust their behaviour (e.g. reducing activity) or physiology (e.g. elevating rates of evaporative water loss) to maintain body temperatures within tolerable limits. The fitness consequences of these adjustments, in terms of the ability to balance water and energy budgets and therefore maintain body condition, are poorly known. We investigated the effects of daily maximum temperature on foraging and thermoregulatory behaviour as well as maintenance of body condition in a wild, habituated population of S outhern P ied B abblers T urdoides bicolor . These birds inhabit a hot, arid area of southern Africa where they commonly experience environmental temperatures exceeding optimal body temperatures. Repeated measurements of individual behaviour and body mass were taken across days varying in maximum air temperature. Contrary to expectations, foraging effort was unaffected by daily maximum temperature. Foraging efficiency , however, was lower on hotter days and this was reflected in a drop in body mass on hotter days. When maximum air temperatures exceeded 35.5 °C, individuals no longer gained sufficient weight to counter typical overnight weight loss. This reduction in foraging efficiency is likely driven, in part, by a trade‐off with the need to engage in heat‐dissipation behaviours. When we controlled for temperature, individuals that actively dissipated heat while continuing to forage experienced a dramatic decrease in their foraging efficiency. This study demonstrates the value of investigations of temperature‐dependent behaviour in the context of impacts on body condition, and suggests that increasingly high temperatures will have negative implications for the fitness of these arid‐zone birds.

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Involvement of the orexin/hypocretin system in ethanol conditioned place preference - Charlene M. Voorhees; Christopher L. Cunningham (Psychopharmacology, 2011)

Characterization of microsatellite loci in the straw-colored fruit bat, Eidolon helvum (Pteropodidae) - Alison J. Peel; Stephen J. Rossiter; James L. N. Wood; Andrew A. Cunningham; David R. Sargan (Conservation Genetics Resources, 2010)

Comparison of the DNA methylation profiles of human peripheral blood cells and transformed B-lymphocytes - Yan V. Sun; Stephen T. Turner; Jennifer A. Smith; Pamela I. Hammond; Alicia Lazarus; Jodie L. Van De Rostyne; Julie M. Cunningham; Sharon L. R. Kardia (Human Genetics, 2010)

Effect of pore velocity on biodegradation of cis-dichloroethene (DCE) in column experiments - Itza Mendoza-Sanchez; Robin L. Autenrieth; Thomas J. McDonald; Jeffrey A. Cunningham (Biodegradation, 2010)

Adjustment of the basin-scale circulation at 26° N to variations in Gulf Stream, deep western boundary current and Ekman transports as observed by the Rapid array - H. L. Bryden; A. Mujahid; S. A. Cunningham; T. Kanzow (Ocean Science, 2009)
The Rapid instrument array across the Atlantic Ocean along 26° N provides unprecedented monitoring of the basin-scale circulation. A unique feature of the Rapid array is the combination of full-depth moorings with instruments measuring temperature, salinity, pressure time series at many depths with co-located bottom pressure measurements so that dynamic pressure can be measured from surface to bottom. Bottom pressure measurements show a zonally uniform rise (and fall) of bottom pressure of 0.015 dbar on a 5 to 10 day time scale, suggesting that the Atlantic basin is filling and draining on a short time scale. After removing the zonally uniform bottom pressure fluctuations, bottom pressure variations at 4000 m depth against the western boundary compensate instantaneously for baroclinic fluctuations in the strength and structure of the deep western boundary current so there is no basin-scale mass imbalance resulting from variations in the deep western boundary current. After removing the mass compensating bottom pressure, residual bottom pressure fluctuations at the western boundary just east of the Bahamas balance variations in Gulf Stream transport. Again the compensation appears to be especially confined close to the western boundary. Thus, fluctuations in either Gulf Stream or deep western boundary current transports are compensated in a depth independent (barotropic) manner very close to the continental slope off the Bahamas. In contrast, compensation for variations in wind-driven surface Ekman transport appears to involve fluctuations in both western basin and eastern basin bottom pressures, though the bottom pressure difference fluctuations appear to be a factor of 3 too large, perhaps due to an inability to resolve small bottom pressure fluctuations after removal of larger zonal average, baroclinic, and Gulf Stream pressure components. For 4 tall moorings where time series dynamic height (geostrophic pressure) profiles can be estimated from sea surface to ocean bottom and bottom pressure can be added, there is no general correlation between surface dynamic height and bottom pressure. Dynamic height on each mooring is strongly correlated with sea surface height from satellite observations and the variability in both dynamic height and satellite sea surface height decrease sharply as the western boundary is approached.

Resource allocation in a social wasp: effects of breeding system and life cycle on reproductive decisions - ELIZABETH L. JOHNSON; TYLER W. CUNNINGHAM; SARAH M. MARRINER; JENNIFER L. KOVACS; BRENDAN G. HUNT; DIMPAL B. BHAKTA; MICHAEL A. D. GOODISMAN (Molecular Ecology, 2009)
Organisms must make important decisions on how to allocate resources to reproduction. We investigated allocation decisions in the social wasp Vespula maculifrons to understand how social insects make reproductive choices. We first determined how annual colonies apportioned resources to growth and reproduction by analysing developing brood. In contrast to expectations, colonies invested in both growth (workers) and reproduction (males) simultaneously. In addition, colonies showed evidence of producing males in pulses and reversing their reproductive choices by decreasing investment in males late in the season. This reversal is consistent with theory suggesting that colonies decrease production in males if fitness of late emerging males is low. To further investigate reproductive decisions within colonies, we determined if the male mates of multiply‐mated queens varied in their reproductive success over time. Sperm use by queens did vary over time suggesting that male success may depend on sperm clumping within the female reproductive tract. Finally, we tested if colony sex ratio conformed to expectations under kin selection theory that nestmate relatedness would positively correlate with investment in new queens if workers controlled sex allocation. Surprisingly, the proportion of queens produced by colonies was negatively correlated with nestmate relatedness, suggesting that allocation may be shaped by advantages arising from increased genetic diversity resulting from multiple mating by queens. Overall, our study suggests that the reproductive decisions of colonies are flexible and may depend both on environmental cues arising from energetic needs of the colony and genetic cues arising from mating behaviours of queens.

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

Parasite species richness in carnivores: effects of host body mass, latitude, geographical range and population density - Patrik Lindenfors; Charles L. Nunn; Kate E. Jones; Andrew A. Cunningham; Wes Sechrest; John L. Gittleman (Global Ecology and Biogeography, 2007)
Aim Comparative studies have revealed strong links between ecological factors and the number of parasite species harboured by different hosts, but studies of different taxonomic host groups have produced inconsistent results. As a step towards understanding the general patterns of parasite species richness, we present results from a new comprehensive data base of over 7000 host–parasite combinations representing 146 species of carnivores (Mammalia: Carnivora) and 980 species of parasites. Methods We used both phylogenetic and non‐phylogenetic comparative methods while controlling for unequal sampling effort within a multivariate framework to ascertain the main determinants of parasite species richness in carnivores. Results We found that body mass, population density, geographical range size and distance from the equator are correlated with overall parasite species richness in fissiped carnivores. When parasites are classified by transmission mode, body mass and home range area are the main determinants of the richness of parasites spread by close contact between hosts, and population density, geographical range size and distance from the equator account for the diversity of parasites that are not dependent on close contact. For generalist parasites, population density, geographical range size and latitude are the primary predictors of parasite species richness. We found no significant ecological correlates for the richness of specialist or vector‐borne parasites. Main conclusions Although we found that parasite species richness increases instead of decreases with distance from the equator, other comparative patterns in carnivores support previous findings in primates, suggesting that similar ecological factors operate in both these independent evolutionary lineages.

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Rapid induction of Pavlovian approach to an ethanol-paired visual cue in mice - Christopher L. Cunningham; Priya Patel (Psychopharmacology, 2007)

A label-free photonic crystal biosensor imaging method for detection of cancer cell cytotoxicity and proliferation - Leo L. Chan; Saujanya L. Gosangari; Kenneth L. Watkin; Brian T. Cunningham (Apoptosis, 2007)

Role of test activity in ethanol-induced disruption of place preference expression in mice - Christina M. Gremel; Christopher L. Cunningham (Psychopharmacology, 2007)

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Feline Immunodeficiency Virus and Puma Lentivirus in Florida panthers (Puma concolor coryi): Epidemiology and Diagnostic Issues - D. L. Miller; S. K. Taylor; D. S. Rotstein; M. B. Pough; M. C. Barr; C. A. Baldwin; M. Cunningham; M. Roelke; D. Ingram (Veterinary Research Communications, 2006)

Patterns of fish deformities and their association with trematode cysts in the Willamette River, Oregon - Michael E. Cunningham; Douglas F. Markle; Virginia G. Watral; Michael L. Kent; Larry R. Curtis (Environmental Biology of Fishes, 2005)

Expanding GSK?s Solvent Selection Guide?application of life cycle assessment to enhance solvent selections - Concepcin Jimnez-Gonzlez; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (Clean Technologies and Environmental Policy, 2004)

Allopregnanolone does not influence ethanol-induced conditioned place preference in DBA/2J mice - Kara I. Gabriel; Christopher L. Cunningham; Deborah A. Finn (Psychopharmacology, 2004)

Vulnerability of mouse cortical neurons to doxorubicin-induced apoptosis is strain-dependent and is correlated with mRNAs encoding Fas, Fas-Ligand, and metalloproteinases - M. Wetzel; J. Tibbitts; G. A. Rosenberg; L. A. Cunningham (Apoptosis, 2004)

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

Cradle-to-gate life cycle inventory and assessment of pharmaceutical compounds - Conceptión Jiménez-González; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2004)

Apparatus bias and place conditioning with ethanol in mice - Christopher L. Cunningham; Nikole K. Ferree; MacKenzie A. Howard (Psychopharmacology, 2003)

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening - Juanliang Cai; Barbara K. Goodman; Ankita S. Patel; John B. Mulliken; Lionel Van Maldergem; George E. Hoganson; William A. Paznekas; Ziva Ben-Neriah; Ruth Sheffer; Michael L. Cunningham; Donna L. Daentl; Ethylin Wang Jabs (Human Genetics, 2003)

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice - Katherine G. Hill; Herminia Alva; Yuri A. Blednov; Christopher L. Cunningham (Psychopharmacology, 2003)

Mechanisms of competition: thermal inhibition of tree seedling growth by grass - Marilyn C. Ball; J. Egerton; Jason L. Lutze; Vincent P. Gutschick; Ross B. Cunningham (Oecologia, 2002)

Distal and proximal pre-exposure to ethanol in the place conditioning task: tolerance to aversive effect, sensitization to activating effect, but no change in rewarding effect - Christopher L. Cunningham; Laura E. Tull; Kirsten E. Rindal; Paul J. Meyer (Psychopharmacology, 2002)

Bridging the gap - V. L. Cunningham (Clean Technologies and Environmental Policy, 1999)

LONG DISTANCE OFFSHORE MOVEMENTS OF BOTTLENOSE DOLPHINS 1 - Randall S. Wells; Howard L. Rhinehart; Petra Cunningham; Joanne Whaley; Melody Baran; Chris Koberna; Daniel P. Costa (Marine Mammal Science, 1999)
A bstract Despite recent progress defining the morphological and genetic characteristics of forms of the bottlenose dolphin inhabiting offshore waters, little is known of their behavior or ranging patterns. Reports suggest that an “offshore form” exists between the 200‐ and 2,000‐m isobaths in distinct Gulf of Mexico and western North Atlantic stocks, while one or more coastal forms inhabit the waters inshore. Two opportunities to track rehabilitated adult male bottlenose dolphins with satellite‐linked transmitters occurred in 1997. “Rudy” stranded in NW Florida and was released in the Gulf of Mexico off central west Florida. He moved around Florida and northward to off Cape Hatteras, NC, covering 2,050 km in 43 d. “Gulliver” stranded near St. Augustine and was released off Cape Canaveral, FL. He moved 4,200 km in 47 d to a location northeast of the Virgin Islands. Gulliver swam through 5,000‐m‐deep waters 300 km offshore of the northern Caribbean islands, against the North Equatorial Current. These records expand the range and habitat previously reported for the offshore stock of bottlenose dolphins inhabiting the waters off the southeastern United States, underscore the difficulties of defining pelagic stocks, illustrate the success of rehabilitation efforts, indicate the value of follow‐up monitoring of rehabilitated and released cetaceans, and expand our understanding of the long‐range movement capabilities of a dolphin species more commonly thought of as a resident in coastal waters.

Genetic differences in cocaine-induced conditioned place preference in mice depend on conditioning trial duration - Christopher L. Cunningham; Shelly D. Dickinson; Nicholas J. Grahame; Dobrina M. Okorn; Carrie S. McMullin (Psychopharmacology, 1999)

GABA A receptors modulate ethanol-induced conditioned place preference and taste aversion in mice - J. A. Chester; Christopher L. Cunningham (Psychopharmacology, 1999)

Extinction of ethanol-induced conditioned place preference and conditioned place aversion: effects of naloxone - Christopher L. Cunningham; Carly M. Henderson; Nancy M. Bormann (Psychopharmacology, 1998)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Flavor preference conditioning by oral self-administration of ethanol - Christopher L. Cunningham; Jill S. Niehus (Psychopharmacology, 1997)

Quaternary alluvial fans in the Gobi of southern Mongolia: evidence for neotectonics and climate change - L. A. Owen; B. F. Windley; W. D. Cunningham; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1997)

Serotonergic mechanisms involved in the discriminative stimulus, reinforcing and subjective effects of cocaine - Sharon L. Walsh; K. A. Cunningham (Psychopharmacology, 1997)

Campbell 14: A verticillium resistant round white potato variety - A. F. Reeves; C. E. Cunningham; R. L. Nickeson; R. V. Akeley; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1985)

Yankee Supreme: A new bruise-resistant potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; R. L. Nickeson; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1984)

The role of male vs male interactions in maintaining population dialect structure - Myron Charles Baker; Daniel B. Thompson; Gregory L. Sherman; Michael A. Cunningham (Behavioral Ecology and Sociobiology, 1981)

Oxidative discoloration of potato tuber tissue related to translucency of processed dice - John F. Kelly; Howard L. Adams; Charles E. Cunningham (American Journal of Potato Research, 1969)

Wauseon: A new potato variety resistant to golden nematode with good processing quality - C. E. Cunningham; R. V. Akeley; L. C. Peterson; T. E. Snyder (American Journal of Potato Research, 1968)

Erratum - I. L. Nonnecke; W. E. Torfason; L. C. Young; P. Nandi; S. P. Raychaudhuri; Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks; Clarence J. Miller; Richard L Sawyer (American Journal of Potato Research, 1966)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Minutes of Executive Committee Meeting, Annual Business Meeting, Committee reports and Financial Report - L. C. Young; Richard L. Sawyer; Hugh J. Murphy; J. W. Scannell; John C. Campbell; Walter C. Sparks; Ora Smith; William B. Raymer; R. H. Treadway; J. C. Campbell; Arthur Hawkins; R. G. Rowberry; et al. (American Journal of Potato Research, 1962)

Report of the potato utilization committee - C. E. Cunningham; O. C. Turnquist; D. R. Isleib; E. J. Wheeler; R. L. Sawyer; P. A. Xander; W. C. Sparks; R. H. Treadway (American Journal of Potato Research, 1959)

Effect of size of plot, experimental design and replication on efficiency of potato fertilizer experiments - G. L. Terman; Mildred R. Covell; C. E. Cunningham (American Journal of Potato Research, 1957)

Effect of date and method of kill on yield, specific gravity and other quality factors of maine potatoes - G. L. Terman; C. E. Cunningham; Michael Goven (American Journal of Potato Research, 1952)

Effect of storage temperature and size on French fry quality, shrinkage and specific gravity of Maine potatoes - G. L. Terman; Michael Goven; C. E. Cunningham (American Journal of Potato Research, 1950)